THE POTENTIAL OF Zinnia elegans AND Bacillus sp. as Lead (Pb) BIOREMEDIATION AGENTS - Febiola, Regina Rosari; Prasetyawati, Endang Triwahyu; Nirwanto , Herry (BRIN - Badan Riset dan Inovasi Nasional, 2025)
Lead (Pb) pollution in soil is a serious problem that reduces crop productivity. One approach to address this issue is through bioremediation and Phytoremediation, using microorganism and plants that can tolerate and bind heavy metals. This study examine the potential of Zinnia elegans (Jacq.) and Bacillus sp., and in combination to reduce Pb in soil. The experiment lasted 60 days using a completely randomized design with six treatments: P0 (control, Pb-contaminated soil without plants or bacteria), P1 (Z. elegans only), P2 (Bacillus sp. only), P3 (combination), P4 (non-contaminated soil with Z. elegans and Bacillus sp.), and P5 (non-contaminated soil with Z. elegans only). The results showed that treatment P3 reduced Pb concentration by 62.31 ppm, while no significant differences were observed among treatments in terms of plant growth parameters. Combining Z. elegans with Bacillus sp. may serve as a practical approach to enhance Pb remediation in contaminated soils.